2012
DOI: 10.1002/adhm.201200073
|View full text |Cite
|
Sign up to set email alerts
|

Mussel‐Inspired Coating of Polydopamine Directs Endothelial and Smooth Muscle Cell Fate for Re‐endothelialization of Vascular Devices

Abstract: Polydopamine (PDAM), a mussel adhesive protein inspired coating that can be easily deposited onto a wide range of metallic, inorganic, and organic materials, gains interest also in the field of biomaterials. In this work, PDAM is applied as coating on 316L stainless steel (SS) stents and the response of cells of the blood vessel wall, human umbilical vein endothelial cell (HUVEC), and human umbilical artery smooth muscle cell (HUASMC) as predictors for re‐endothelialization is tested. It is found that the PDAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 48 publications
3
115
0
Order By: Relevance
“…7a). The promotion of the growth of HUASMCs was not consistent with the previous investigation of PDAM modification on 316L stainless steel stents [45]. Considering the substrates, the PLLA was not very suitable for cell growth.…”
Section: Huasmc Adhesion and Proliferation With Direct Incubation On supporting
confidence: 48%
“…7a). The promotion of the growth of HUASMCs was not consistent with the previous investigation of PDAM modification on 316L stainless steel stents [45]. Considering the substrates, the PLLA was not very suitable for cell growth.…”
Section: Huasmc Adhesion and Proliferation With Direct Incubation On supporting
confidence: 48%
“…More importantly, polydopamine coating exhibits strong reactivity towards various nucleophiles with amine and thiol groups due to the presence of quinone after polymerization [3637]. Thus, proteins containing large amounts of amine and thiol groups have been successfully conjugated through polydopamine coating for various applications, such as enzyme immobilization and stem cell manipulation [3839]. Covalent immobilization of collagen onto titanium surfaces was achieved by coupling collagen with a preformed polydopamine coating with the aid of EDC and NHS.…”
Section: Discussionmentioning
confidence: 99%
“…As a simple, versatile, and effective strategy to promote cell adhesion onto substrates with various material type and shape under solvent-free and non-toxic condition, polydopamine (PDA) films has attracted much attention in the field of biomaterials surface modification since Lee et al reported it in 2007 [41] . In the field of vascular biomaterials, PDA coating has been used as an immobilization layer for vascular endothelial growth factor (VEGF) [42,43] , heparin [44,45] , etc., and has also been used to control cell behaviors directly on the surface, which demonstrated that human umbilical vein endothelial cells (HUVECs) could adhere well and spread with a high viability on PDA coating [46][47][48] ; moreover, it showed that PDA coating on 316L stainless steel stent decreased adhesion and proliferation [48] .…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…[47] ; on the other hand, it could facilitate the secretion, deposition and assembly of endogenous fibronectin (Fn), resulting in the formation of Fn fibril colocalizing with α 5 β 1 integrin, which plays a key role in the adhesion of HUVECs on PDA [46] . As to the effect of PDA coating on vascular smooth muscle cells (VSMCs) [48] , inhibition of VSMCs' adhesion and proliferation was demonstrated compared to the 316L stainless steel control. In contrast, PDA layer on MgF 2 surface in the present study did not show VSMC inhibition effect.…”
Section: Cells Reaction To the Hf-pda-treated Magnesium Alloy In Vitromentioning
confidence: 99%